1991
DOI: 10.1128/aem.57.4.962-968.1991
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of nitroaromatic compounds by anaerobic bacteria isolated from the human gastrointestinal tract

Abstract: Human intestinal microbial flora were screened for their abilities to reduce nitroaromatic compounds by growing them on brain heart infusion agar plates containing 1-nitropyrene. Bacteria metabolizing 1-nitropyrene, detected by the appearance of clear zones around the colonies, were identified as Clostridium leptum, Clostridium paraputrificum, Clostridium clostridiiforme, another Clostridium sp., and a Eubacterium sp. These bacteria produced aromatic amines from nitroaromatic compounds, as shown by thin-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…The reduction of TNT and various other nitroaromatic compounds by Pseudomonas species under aerobic (20) and anaerobic conditions by a sulfate-reducing bacterium was described previously (17). Nitroreductases have been found in members of the genera Enterobacter (6), Nocardia (35), and Neurospora (37) and anaerobic bacteria of the human gastrointestinal tract (18). Nitroreductase activity of P. chrysosporium was mentioned by Valli et al (34) for the reduction of 2,4-dinitrotoluene.…”
Section: Discussionmentioning
confidence: 92%
“…The reduction of TNT and various other nitroaromatic compounds by Pseudomonas species under aerobic (20) and anaerobic conditions by a sulfate-reducing bacterium was described previously (17). Nitroreductases have been found in members of the genera Enterobacter (6), Nocardia (35), and Neurospora (37) and anaerobic bacteria of the human gastrointestinal tract (18). Nitroreductase activity of P. chrysosporium was mentioned by Valli et al (34) for the reduction of 2,4-dinitrotoluene.…”
Section: Discussionmentioning
confidence: 92%
“…and showed a relationship with Clostridium acetobutylicum and Clostridium thermoaceticum . It has been reported that C. acetobutylicum and C. thermoaceticum could reduce the nitro group of nitroaromatics to the corresponding amines (Rafii et al , 1991; Gorontzy et al , 1993; Khan et al , 1997; Huang et al , 2000). These results suggest that Clostridium may play a role in reduction of the nitro group of nitrobenzene in polluted sediments of this study.…”
Section: Resultsmentioning
confidence: 99%
“…reported to undergo gut bacteria-mediated nitro reduction, resulting in the formation of primary amine metabolites (Koch et al, 1980;Elmer and Remmel, 1984;Takeno et al, 1990). Clostridium and Eubacterium have been identified from human intestinal microbial flora as the anaerobic bacteria capable of producing nitroreductases and reducing nitro aromatic compounds (Rafil et al, 1991).…”
Section: Downloaded Frommentioning
confidence: 99%